Persepsi Konsumen Dalam Pembelian Motor Yamaha Fino Pada PD. Panca Motor Kota Jambi - Pupu Sopini (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2020)
This research aims to know and analyze consumers ' perception of Yamaha Fino Motor purchase in PD dealers. Panca Motor Kota Jambi. Research methods used using descriptive analysis and data types are processed from primary data that is deployed on Yamaha Fino motorcycle users. Population and samples amounted to 101 people and were obtained from the number of motorcycles sales in 2018 with sample withdrawals using the census method. The theoretical approach used is the consumer perception theory of Yamaha Fino motor products. Indicators of consumer perception used consist of selection perception, organizing perception and achievement accomplishment. The results showed that consumer perception in Yamaha Fino motorcycle purchases was influenced by the organizing indicators perception with an average score of 408. Consumer perception in the purchase of Yamaha Fino motorcycles was influenced by family stimuli, the environment and the highest because of the promotion carried out by the motor dealers very well with a score of 443.